Tumor-derived exosomes induce CD8+ T cell suppressors. Issue 1 (15th August 2017) - Maybruck, Brian T.; Pfannenstiel, Lukas W.; Diaz-Montero, Marcela; Gastman, Brian R.
Abstract : Background: The suppressive nature of immune cells in the tumor microenvironment plays a major role in regulating anti-tumor immune responses. Our previous work demonstrated that a soluble factor from tumor cells is able to induce a suppressor phenotype (SP) in human CD8 + T cells typified by loss of CD27/CD28 expression and acquisition of a potent suppressor function. The present study hypothesized that the soluble mechanism that is inducing the SP in CD8 + T cells are tumor-derived exosomes (TDEs). Methods: Membrane vesicles and TDEs from multiple head and neck cancer cell line's conditioned growth media were isolated by ultracentrifugation and precipitation, respectively. Human purified CD3 + CD8 + T cells were assessed for their induction of the T cell SP by flow cytometry identifying loss of CD27/CD28 expression and in vitro suppression assays. Furthermore, the T cell SP was characterized for the attenuation of IFN-γ production. To delineate exosomal proteins contributing to T cell SP, mass spectrometry was used to identify unique proteins that were present in TDEs. CRISPR/Cas9 knockout constructs were used to examine the role of one of these proteins, galectin-1. To assess the role of exosomal RNA, RNA purified from TDEs was nucleofected into CD8 + T cells followed by suppression analysis. Results: Using fractionated conditioned growth media, factors >200 kDa induced CD8 + T cell SP, which was determined to be an exosome by mass spectrometry analysis. Multiple head and neck cancer-derived cell lines were found to secrete T cell SP-inducing exosomes. Mass spectrometry analysis revealed that an immunoregulatory protein, galectin-1 (Gal-1), was expressed in those exosomes, but not in TDEs unable to induce T cell SP. Galectin-1 knockout cells were found to be less able to induce T cell SP. Furthermore, RNA purified from the T cell SP-inducing exosomes were found to partially induce the SP when transfected into normal CD8 + T cells. Conclusions: For the first-time, TDEs have been identified to induce a SP in CD8 + T cells and their mode of action may be synergistic effects from exosomal proteins and RNA. One protein in particular, galectin-1, appears to play a significant role in inducing T cell SP. Therefore, tumor-derived immunosuppressive exosomes are a potential therapeutic target to prevent T cell dysfunction and enhance anti-tumor immune responses.